Perilaku Organisasi dan Budaya Ketergantungan Terhadap Sistem Informasi Di Era Modern - Ribi Tri Amanda; Muhammad Irwan Padli Nasution (Getpress Management Journals, 2025)
The rapid advancement of information technology has fundamentally transformed the ways in which organizations operate, communicate, and make strategic decisions. This article aims to analyze the degree of organizational dependence on information systems in the modern era and examine its impact on operational effectiveness and competitive sustainability. Using a literature study method, this research reviews various empirical and conceptual findings regarding the role of information systems in enhancing work efficiency, strengthening inter-unit integration, and accelerating decision-making processes. The findings indicate that organizational dependence on information systems continues to increase in line with the growing complexity of data needs and the dynamic demands of the market. The analysis further reveals that information systems play a significant role in improving process speed, information accuracy, and internal coordination, while also introducing risks such as cyberattacks, system failures, and user resistance to technological changes. The implications of these findings highlight the importance of implementing risk management strategies, strengthening information security, and developing adaptive human resources to ensure that this dependence becomes a source of organizational strength rather than vulnerability. Thus, information systems are not merely operational support tools but have become a strategic foundation for organizational sustainability, resilience, and competitive advantage in the digital era.